Sealing glass powder for flat plate type solid oxide fuel cell and preparation method of sealing glass powder

By using boron, phosphorus and silicate mixed system glass in solid oxide fuel cells, the problem of insufficient stability and fluidity of existing glass materials at high temperatures is solved, and better chemical stability and fluidity is achieved, and it is suitable for sealing materials of high-temperature SOFC.

CN119797763APending Publication Date: 2025-04-11福赛尔(武汉)集成有限公司
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411949727.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

When used in solid oxide fuel cells, existing phosphate, borate and silicate-based glass materials have problems such as poor volatility, obvious interface reaction, poor acid resistance, alkali resistance and water resistance, which limits their application in high-temperature SOFC.

Method used

Using a mixed system glass of boron, phosphorus and silicate, a sealing glass powder with stability and good fluidity is designed by reasonably matching the ratio of B2O3, P2O5 and SiO2. The composition of the glass powder includes SiO2 25% to 35% by weight, P2O5 20% to 30% by weight, B2O3 1% to 10% by weight, etc., and is obtained by a specific preparation method.

Benefits of technology

It has achieved good chemical stability, acid resistance, alkali resistance and water resistance of glass materials at high temperatures. It is suitable for sealing materials of high temperature SOFC, and has better sealing fluidity and a wider range of applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119797763A_ABST
    Figure CN119797763A_ABST
Patent Text Reader

Abstract

The invention discloses sealing glass powder for a flat plate type solid oxide fuel cell and a preparation method of the sealing glass powder. The glass sealing powder for the solid oxide fuel cell is prepared from the following raw materials in percentage by mass: 25 to 35 weight percent of SiO2, 20 to 30 weight percent of P2O5, 1 to 10 weight percent of B2O3, 1 to 5 weight percent of Al2O3, 0.1 to 5 weight percent of CaO, 5 to 15 weight percent of MgO, 0.1 to 2 weight percent of Li2O, 0.1 to 5 weight percent of Na2O, 0.1 to 7 weight percent of K2O, 5 to 10 weight percent of ZnO, 0.1 to 5 weight percent of Y2O3 and 0.1 to 5 weight percent of La2O3. And practical and industrial conditions can be achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of solid oxide fuel cells, and in particular to a sealing glass powder for a flat solid oxide fuel cell and a preparation method thereof. Background Art

[0002] Solid oxide fuel cell (SOFC) can directly convert chemical energy into electrical energy. Compared with traditional energy conversion devices, fuel cells have high energy conversion efficiency, cleanness, no noise pollution, and can be designed into a modular structure with high specific power. It is called the fourth generation of power generation technology after water power, thermal power, and nuclear power and a power device to replace internal combustion engines. The international energy community predicts that fuel cells are one of the most attractive power generation technologies in the 21st century.

[0003] So far, domestic and foreign researchers have conducted extensive research on various fields related to planar SOFC, and have explored in depth the changes in the microstructure and interface reactions of each cell component and the interface between components under long-term working conditions. In order to obtain a SOFC stack with high output power density and stability, a dense and stable sealing material is essential. Glass is often used as a sealing material for SOFC due to its simple, flexible, low-cost and adjustable performance.

[0004] Patent CN101597136A of Suzhou Hengcang Infrared Optical Materials Research and Development Center Co., Ltd. discloses a P2O5-B2O3-ZnO-TeO2 sealing glass with a softening temperature of 420-470°C and a thermal expansion coefficient of (65-130)×10 -7 / ℃, the phosphate glass of this system can only be used as a sealing material for medium and low temperature SOFC. In addition, the acid resistance, alkali resistance and water resistance of phosphate glass are generally poor, which greatly limits its application in SOFC.

[0005] In terms of sealing materials, the glass systems are mainly concentrated in the phosphorus, boron and silicate systems. (1) Phosphate series: At the operating temperature of the solid oxide microplate fuel, the phosphate volatilizes and easily reacts with the anode at the interface to form nickel phosphate and zirconium phosphate, which reduces the activity of the anode. At the same time, the stability of the crystals formed by phosphate glass in a humid fuel atmosphere is also not ideal. (2) Borate system: The significant volatilization of B2O3 under high temperature conditions restricts the application of borate glass in solid oxide fuel cell sealing materials. Studies have found that this type of glass causes significant weight loss due to volatilization, and the interface reaction that occurs is also very obvious. (3) Silicate system: Relatively speaking, silicate-based glass materials have weaker volatility and stronger sealing stability, but poorer sealing fluidity.

[0006] Therefore, there is an urgent need for a sealing glass material for solid oxide fuel cells that has stability and temperature resistance. Summary of the invention

[0007] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a sealing glass powder for a planar solid oxide fuel cell and a preparation method thereof. The method uses a boron, phosphorus, and silicate mixed system glass, which has both the stability of a silicate glass system and good fluidity, meeting the use requirements of solid oxide fuel cell sealing materials.

[0008] To achieve the above purpose, the technical solution designed by the present invention is as follows:

[0009] The present invention provides a sealing glass powder for a flat solid oxide fuel cell. Calculated by mass percentage, the raw material composition of the glass sealing powder includes SiO2: 25wt%-35wt%, P2O5: 20wt%-30wt%, B2O3: 1wt%-10wt%, Al2O3: 1wt%-5wt%, CaO: 0.1wt%-5wt%, MgO: 5wt%-15wt%, Li2O: 0.1wt%-2wt%, Na2O: 0.1wt%-5wt%, K2O: 0.1wt%-7wt%, ZnO: 5wt%-10wt%, Y2O3: 0.1wt%-5wt% and La2O3: 0.1wt%-5wt%.

[0010] Furthermore, calculated by mass percentage, the raw material composition of the glass sealing material includes: SiO2: 25wt% ~ 28wt%, P2O5: 25wt% ~ 30wt%, B2O3: 2wt% ~ 6wt%, Al2O3: 3wt% ~ 5wt%, CaO: 1wt% ~ 3wt%, MgO: 12wt% ~ 15wt%, Li2O: 0.1wt% ~ 1wt%, Na2O: 2wt% ~ 3wt%, K2O: 3wt% ~ 4wt%, ZnO: 8wt% ~ 10wt%, Y2O3: 1wt% ~ 2wt% and La2O3: 3wt% ~ 5wt%.

[0011] Furthermore, calculated by mass percentage, the raw material composition of the glass sealing material includes: SiO2: 25wt%, P2O5: 25wt%, B2O3: 6wt%, Al2O3: 5wt%, CaO: 3wt%, MgO: 12wt%, Li2O: 1wt%, Na2O: 3wt%, K2O: 3wt%, ZnO: 10wt%, Y2O3: 2wt% and La2O3: 5wt%.

[0012] Furthermore, the expansion coefficient of the sealing glass powder for the solid oxide fuel cell is 9.9×10 -6 ~10.2×10 -6 / K, the glass transition temperature is 635~656℃.

[0013] The present invention also provides a method for preparing the sealing glass powder for solid oxide fuel cells, comprising the following steps:

[0014] (1) Ingredients: weigh the raw materials according to the above mass percentages;

[0015] (2) Mixing: Mix the weighed raw materials evenly;

[0016] (3) Melting: placing the powder in an air atmosphere of a box-type resistance furnace and heating it to obtain molten glass;

[0017] (4) Water quenching: pouring the glass liquid into cold water for water quenching to obtain glass material;

[0018] (5) Ball milling and screening: The glass material obtained by water quenching is ball milled, screened, and dried to obtain the sealing glass powder for solid oxide fuel cells.

[0019] Furthermore, in the step (2), the mixing time is 30 to 60 minutes.

[0020] Furthermore, in the step (3), the powder is placed in a platinum crucible, the crucible is covered, and the crucible is placed in an air atmosphere of a box-type resistance furnace; the heating conditions are: heating to 1350-1500°C at a heating rate of 4-6°C / min, and keeping warm for 0.5-1h.

[0021] Furthermore, the glass liquid obtained in step (3) was placed in a muffle furnace at 600°C for 30 min to anneal the glass block, and the glass block was cut into long strips using a diamond wire cutting machine. The expansion coefficient was tested to be 9.9×10 -6 ~10.2×10 -6 / K.

[0022] Furthermore, in the step (5), the product is sieved through 200 mesh and dried at 85° C. for 240 min.

[0023] The present invention also provides an application of the glass sealing powder in preparing a solid oxide fuel cell.

[0024] Principle of the present invention:

[0025] In the sealing glass powder of the present invention, B2O3 has the effect of lowering the softening point of glass, improving the sealing fluidity of glass and lowering the melting temperature of glass. P2O5 can give glass low melting performance, but too high a content will increase the thermal expansion coefficient of glass and reduce chemical stability. SiO2, as a network former of glass, forms an irregular network connection in the glass with the structure of [SiO4] tetrahedron, forming the skeleton of glass. SiO2 can lower the thermal expansion coefficient of glass, improve the thermal stability, chemical stability, heat resistance, hardness, mechanical strength and viscosity of glass, but if the SiO2 content is too high, a higher melting temperature is required.

[0026] Beneficial effects of the present invention:

[0027] (1) The present invention achieves that the glass has an expansion coefficient and an operating temperature that match the sealing requirements of solid fuel cells by reasonably matching the proportions of B2O3, P2O5, and SiO2, and the composition can be flexibly adjusted according to actual process requirements, with relatively strong adjustability.

[0028] (2) Compared with phosphate glass, the sealing glass of the present invention has better acid resistance, alkali resistance and water resistance, higher sealing temperature and wider application range.

[0029] (3) Compared with silicate glass, the sealing glass of the present invention requires a lower temperature when heated and melted, that is, the sealing fluidity is better.

[0030] (4) The raw materials selected in the present invention are all common substances, simple, easy to obtain, and the preparation process is stable. The corresponding oxides are selected as source materials, which has low cost, simple and feasible process, and is easy to realize industrialization. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a graph showing the expansion coefficient of sealing glass for solid oxide fuel cells. DETAILED DESCRIPTION

[0032] The present invention is further described in detail below in conjunction with specific embodiments so that those skilled in the art can understand.

[0033] A sealing glass for a planar solid oxide fuel cell, the composition of which is expressed by the following chemical formula:

[0034] SiO2: 25wt% to 35wt%, P2O5: 20wt% to 30wt%, B2O3: 1wt% to 10wt%, Al2O3: 1wt% to 5wt%, CaO: 0.1wt% to 5wt%, MgO: 5wt% to 15wt%, Li2O: 0.1wt% to 2wt%, Na2O: 0.1wt% to 5wt%, K2O: 0.1wt% to 7wt%, ZnO: 5wt% to 10wt%, Y2O3: 0.1wt% to 5wt% and La2O3: 0.1wt% to 5wt%. Among them, SiO2, P2O5, B2O3, CaO, MgO, ZnO, Na2O and K2O are the main components of glass. The expansion coefficient of the glass is 9.9×10 -6 ~10.2×10 -6 / K, the transition temperature Tg is in the range of 635~656℃.

[0035] The molten glass was cast into blocks, annealed at 600°C for 30 min to eliminate glass profits, and the glass blocks were cut into 25mm×6mm×6mm strips using a wire cutting machine. The expansion coefficient of the glass was tested using an expansion coefficient tester at a heating rate of 5°C / min, and the transition point temperature Tg of the glass was calculated using the expansion coefficient curve obtained from the test.

[0036] The present invention is further described by the following specific examples.

[0037] Example 1

[0038] Preparation of sealing glass powder 1 for planar solid oxide fuel cells

[0039] (1) Ingredients: According to the proportions of the components in Table 1, weigh a certain amount of analytically pure raw materials (SiO2, CaCO3, SrCO3, Al2O3, B2O3, NH4H2PO4, Mg(OH)2, ZnO, K2CO3, Na2CO3, Li2CO3, Y2O3, La2O3);

[0040] (2) Mixing: Mix the weighed raw materials using a three-dimensional mixer for 30 minutes to obtain a powder;

[0041] (3) Melting: Put the powder into a platinum crucible, cover the crucible, place it in an air atmosphere in a box-type resistance furnace, heat it to 1350°C at 5°C / min, and keep it warm for 1 hour to obtain glass liquid;

[0042] (4) Testing the expansion coefficient: The glass liquid obtained in step (3) is poured into a mold to cast into a glass block, which is then placed in a muffle furnace and kept at 600° C. for 30 min to anneal the glass block. The glass block is cut into strips of 25 mm×6 mm×6 mm using a diamond wire cutter, and the expansion coefficient is tested.

[0043] (5) Water quenching: pouring the glass liquid into cold water for water quenching to obtain glass material;

[0044] (6) Ball milling and sieving: The glass material obtained by water quenching is ball milled, passed through a 200-mesh sieve, and dried at 85° C. for 240 min to obtain a sealing glass powder 1 for a planar solid oxide fuel cell;

[0045] Example 2

[0046] Preparation of Sealing Glass Powder 2 for Planar Solid Oxide Fuel Cells

[0047] The preparation method of this embodiment is the same as that of embodiment 1, except that the amount of raw materials used is different and the melting temperature is 1400°C.

[0048] Example 3

[0049] Preparation of sealing glass powder 3 for planar solid oxide fuel cells

[0050] The preparation method of this embodiment is the same as that of embodiment 1, except that the amount of raw materials used is different and the melting temperature is 1500°C.

[0051] Comparative Example 1 and Comparative Example 2

[0052] The preparation methods of Comparative Example 1 (silicate glass) and Comparative Example 2 (phosphate glass) are the same as those of Example 1, the only difference being the amount of raw materials used, as shown in Table 1.

[0053] Table 1 Mass percentage composition of the glasses prepared in Examples 1 to 3

[0054] <![CDATA[SiO2]]> <![CDATA[Al2O3]]> <![CDATA[P2O5]]> <![CDATA[B2O3]]> MgO CaO ZnO <![CDATA[K2O]]> <![CDATA[Na2O]]> <![CDATA[Li2O]]> <![CDATA[Y2O3]]> <![CDATA[La2O3]]> Example 1 25 5 30 1.7 15 0.1 10 5 3 0.1 0.1 5 Example 2 25 5 25 6 12 3 10 3 3 1 2 5 Example 3 30 3 20 10 10 5 8 3 2 2 5 2 Comparative Example 1 40 5 15 15 3 6 6 2 8 Comparative Example 2 3.3 37 29.9 8 9.2 5.9 4.2 1.5 1

[0055] Table 2 Expansion coefficients of sealing glasses of Examples 1 to 3 and their related temperatures

[0056] Expansion coefficient Glass transition temperature (Tg) Glass powder sealing temperature (lg4) Example 1 <![CDATA[10.2×10 -6 / K]]> 635℃ 837℃ Example 2 <![CDATA[10.1×10 -6 / K]]> 644℃ 843℃ Example 3 <![CDATA[9.9×10 -6 / K]]> 656℃ 845℃ Comparative Example 1 <![CDATA[9.8×10 -6 / K]]> 680℃ 992℃ Comparative Example 2 <![CDATA[10.8×10 -6 / K]]> 498℃ 794℃

[0057] From Table 2 and Figure 1 It can be seen from the figure that under the condition of relatively close expansion coefficients, the sealing temperature of phosphate glass is very low (794°C), and it is difficult to maintain a sealed state under the operating temperature of the solid oxide fuel cell; while the sealing temperature of silicate glass is very high (992°C), which will produce disadvantages of high energy consumption and long time in practical applications. Compared with the two glass formulas of the above-mentioned comparative examples 1 to 2, the expansion coefficient of the sealing glass powder for the planar solid oxide fuel cell prepared in Examples 1 to 3 is 9.9×10 -6 ~10.2×10 -6 / K, the transition temperature is 635-656°C, the sealing temperature is 837-845°C, and the sealing glass powder prepared in Example 2 has the best effect.

[0058] In summary, the present invention realizes the sealing of solid oxide fuel cells at a lower cost and in a shorter time. The present invention obtains a sealing glass matching a planar solid oxide fuel cell through the above embodiments, which has good sealing fluidity and high-temperature chemical stability. Its significant effect is mainly reflected in the improvement of high-temperature chemical stability.

[0059] Although the above embodiments have been described in detail, they are only a part of the embodiments of the present invention, not all of them. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all belong to the protection scope of the present invention.

Claims

1. A sealing glass powder for a planar solid oxide fuel cell, characterized in that: Calculated by mass percentage, the raw material composition of the glass sealing powder includes: SiO2: 25wt% ~ 35wt%, P2O5: 20wt% ~ 30wt%, B2O3: 1wt% ~ 10wt%, Al2O3: 1wt% ~ 5wt%, CaO: 0.1wt% ~ 5wt%, MgO: 5wt% ~ 15wt%, Li2O: 0.1wt% ~ 2wt%, Na2O: 0.1wt% ~ 5wt%, K2O: 0.1wt% ~ 7wt%, ZnO: 5wt% ~ 10wt%, Y2O3: 0.1wt% ~ 5wt% and La2O3: 0.1wt% ~ 5wt%.

2. The sealing glass powder according to claim 1, characterized in that: Calculated by mass percentage, the raw material composition of the glass sealing material includes: SiO2: 25wt% ~ 28wt%, P2O5: 25wt% ~ 30wt%, B2O3: 2wt% ~ 6wt%, Al2O3: 3wt% ~ 5wt%, CaO: 1wt% ~ 3wt%, MgO: 12wt% ~ 15wt%, Li2O: 0.1wt% ~ 1wt%, Na2O: 2wt% ~ 3wt%, K2O: 3wt% ~ 4wt%, ZnO: 8wt% ~ 10wt%, Y2O3: 1wt% ~ 2wt% and La2O3: 3wt% ~ 5wt%.

3. The sealing glass powder according to claim 2, characterized in that: Calculated by mass percentage, the raw material composition of the glass sealing material includes: SiO2: 25wt%, P2O5: 25wt%, B2O3: 6wt%, Al2O3: 5wt%, CaO: 3wt%, MgO: 12wt%, Li2O: 1wt%, Na2O: 3wt%, K2O: 3wt%, ZnO: 10wt%, Y2O3: 2wt% and La2O3: 5wt%.

4. The sealing glass powder according to any one of claims 1 to 3, characterized in that: The expansion coefficient of the sealing glass powder for solid oxide fuel cells is 9.9×10 -6 ~10.2×10 -6 / K, the glass transition temperature is 635~656℃.

5. A method for preparing the sealing glass powder for solid oxide fuel cells according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) Ingredients: weigh the raw materials according to the above mass percentages; (2) Mixing: Mix the weighed raw materials evenly; (3) Melting: placing the powder in an air atmosphere of a box-type resistance furnace and heating it to obtain molten glass; (4) Water quenching: pouring the glass liquid into cold water for water quenching to obtain glass material; (5) Ball milling and screening: The glass material obtained by water quenching is ball milled, screened, and dried to obtain the sealing glass powder for solid oxide fuel cells.

6. The preparation method according to claim 5, characterized in that: In the step (2), the mixing time is 30 to 60 minutes.

7. The preparation method according to claim 5, characterized in that: In the step (3), the powder is placed in a platinum crucible, the crucible is covered, and the crucible is placed in an air atmosphere of a box-type resistance furnace; the heating conditions are: heating to 1350-1500° C. at a heating rate of 4-6° C. / min, and keeping warm for 0.5-1 h.

8. The preparation method according to claim 5, characterized in that: The glass liquid obtained in step (3) was placed in a muffle furnace at 600°C for 30 min to anneal the glass block, and the glass block was cut into long strips using a diamond wire cutter. The expansion coefficient was tested to be 9.9×10 -6 ~10.2×10 -6 / K.

9. The preparation method according to claim 5, characterized in that: In the step (5), the product is sieved through 200 mesh and dried at 85°C for 240 min.

10. Use of the glass sealing powder as claimed in claim 1 in preparing a solid oxide fuel cell.

Citation Information

Patent Citations

  • Lead-free low-melting sealing glass and preparation method thereof

    CN101597136A